Can commercial buildings cope with Australian bushfires? An IAQ analysis - Arianna Brambilla; Christhina Candido; Marco Filipppo Sangiorgio; Ozgur Gocer; Kenan Gocer (Buildings & Cities, 2021)
The Australian 2019/20 summer witnessed an extraordinary bushfire season characterised by unprecedented duration, geographical reach and impact. The aftermath of the bushfires includes increased health-related implications on people due to short and long exposure to poor air quality. The current advice from the Australian authorities in such events is to remain indoors, as it was assumed indoor air quality (IAQ) is healthy. This paper examined that assumption and presents the case study of an office building in Canberra subjected to the 2019/20 bushfires, responding to the need of understanding the ability of air-conditioning buildings to cope with such unprecedented and extreme weather events. Measured data for indoor concentration of CO2, PM10 and PM2.5 recorded a prolonged period of concerning levels, as well as extreme concentration peaks. This poses a significant risk to the occupants’ health. The values showed peaks up to 12 times higher for PM10 and 24 times higher for PM2.5 than the recommended critical thresholds. The infiltration factor and protection performance analysis suggest that old filtering systems and low airtightness levels are not optimal in protecting the indoor environment from outdoor air pollutants.  'Practice relevance' Results show that the concentration of the outdoor pollutant significantly exceeded thresholds for a prolonged time, posing a health risk to the population. The case study presented has been partially able to protect its occupants thanks to the heating, ventilation and air-conditioning (HVAC) response, but this brings up the concern about all those spaces where mechanical ventilation may not be installed or have the same filtering system. Evidence provided here calls for an urgent update of the protection agenda to account for extreme weather events with regard to the diverse indoor built environments, because relying on the mechanical ventilation system is no more sufficient to provide healthy and safe environments.